Peningkatan Kualitas Desain dan Foto Produk Sandal Spon Aldiva di Desa Karangrejo Kecamatan Gempol Kabupaten Pasuruan - Listin Fitrianah; Agus Rachmad Purnama; Zahrotul Azizah (Abdi-mesin: Jurnal Pengabdian Masyarakat Teknik Mesin, 2021)
This service aims to design training and product photos to increase the production of sponge sandals by aldiva sponge sandal craftsman partners located in Karangrejo Village, Bangil District, Pasuruan Regency. So far, the designs are based on the designs and models of sandals from consumers. Partners do not yet have the characteristics of their own sandal designs and models because human resources in the production department do not yet have the expertise to develop sandal model designs. In addition, the photos uploaded on social media as marketing media are classified as ordinary so that they are less attractive to consumers. This activity uses a contextual approach method, namely the speaker explains the theory first, then proceeds with the practice of taking photos of sandal products by taking the right angle by partners. The results obtained during the training were enthusiastic participants and gained new knowledge.